2014
DOI: 10.1128/jvi.01286-14
|View full text |Cite
|
Sign up to set email alerts
|

Locking and Blocking the Viral Landscape of an Alphavirus with Neutralizing Antibodies

Abstract: Alphaviruses are serious, sometimes lethal human pathogens that belong to the family Togaviridae. The structures of human Venezuelan equine encephalitis virus (VEEV), an alphavirus, in complex with two strongly neutralizing antibody Fab fragments (F5 and 3B4C-4) have been determined using a combination of cryo-electron microscopy and homology modeling. We characterize these monoclonal antibody Fab fragments, which are known to abrogate VEEV infectivity by binding to the E2 (envelope) surface glycoprotein. Both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
45
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 35 publications
2
45
0
1
Order By: Relevance
“…The structures of CHIK-VLPs and also of other alphaviruses had shown that the B domain of glycoprotein E2 covers and protects the fusion loop in domain II of E1 (6,7,12). However, the B domain is exceedingly flexible (8,15) as observed in the crystal structure of the E1E2 heterodimer (14) or the (E1E2) 3 trimer (15).…”
Section: Fitting the Fab Fragments Into The Cryo-em Densitiesmentioning
confidence: 95%
See 2 more Smart Citations
“…The structures of CHIK-VLPs and also of other alphaviruses had shown that the B domain of glycoprotein E2 covers and protects the fusion loop in domain II of E1 (6,7,12). However, the B domain is exceedingly flexible (8,15) as observed in the crystal structure of the E1E2 heterodimer (14) or the (E1E2) 3 trimer (15).…”
Section: Fitting the Fab Fragments Into The Cryo-em Densitiesmentioning
confidence: 95%
“…Most antibodies against alphaviruses target the E2 glycoprotein, since it covers much of E1 and is therefore far more exposed. The two most common mechanisms for neutralizing alphaviruses are by binding to the A domain of E2 and therefore blocking receptor attachment (9)(10)(11)(12) and by preventing exposure of the E1 fusion loop by stabilizing the E2 B domain to cover and protect the fusion loop in the mature virus (9,12). This can be achieved by binding the flexible B domain to the rigid A domain via a Fab fragment (8,12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Three of these antibodies (m10, m242, and CHK-9) bound to the putative receptor binding sites, whereas one, CHK-152, inhibited the exposure of the fusion loop by immobilizing the E2-B domain (22). Analogous structural studies have been reported for other alphaviruses, such as Ross River virus (27), Sindbis virus (33), and VEEV (34). However, there are no published structures of CHIKV in complex with human antibodies.…”
Section: Significancementioning
confidence: 84%
“…The 4UOM structure is described as the F5 Fab bound to the alphavirus Venezuelan equine encephalitis virus (VEEV) and is described in Porta et al (2014).…”
Section: Analysis Of the Blast Resultsmentioning
confidence: 99%